Pyrolytic characteristics and kinetics of pistachio shell by thermogravimetric analysis - Acikalin, Korkut (SPRINGER, 2012)
Pyrolytic characteristics and kinetics of pistachio shell were studied using a thermogravimetric analyzer in 50-800 degrees C temperature range under nitrogen atmosphere at 2, 10, and 15 degrees C min(-1) heating rates. Pyrolysis process was accomplished at four distinct stages which can mainly be attributed to removal of water, decomposition of hemicellulose, decomposition of cellulose, and decomposition of lignin, respectively. The activation energies, pre-exponential factors, and reaction orders of active pyrolysis stages were calculated by Arrhenius, Coats-Redfern, and Horowitz-Metzger model-fitting methods, while activation energies were additionaly determined by Flynn-Wall-Ozawa model-free method. Average activation energies of the second and third stages calculated from model-fitting methods were in the range of 121-187 and 320-353 kJ mol(-1), respectively. The FWO method yielded a compatible result (153 kJ mol(-1)) for the second stage but a lower result (187 kJ mol(-1)) for the third stage. The existence of kinetic compensation effect was evident.
Keywords: Pistachio shell; Thermogravimetric analysis; Pyrolysis kinetics; Coats-Redfern method; Horowitz-Metzger method; Flynn-Wall-Ozawa method; BIOMASS; ATMOSPHERES; ANALYZER; NITROGEN; OIL; Thermodynamics; Chemistry